Facile synthesis of biogenic palladium nanoparticles using biomass strategy and application as photocatalyst degradation for textile dye pollutants and their in-vitro antimicrobial activity. (November 2022) - Liang, Yunyi; Demir, Halit; Wu, Yingji; Aygun, Aysenur; Elhouda Tiri, Rima Nour; Gur, Tugba; Yuan, Yan; Xia, Changlei; Demir, Canan; Sen, Fatih; Vasseghian, Yasser
Abstract: Among biological applications, plant-mediated Pd NPs for multi-drug resistance (MDR) developed in pathogenic bacteria were synthesized with the help of biomass of lemon peel, a biological material, with a non-toxic, environmentally friendly, human-nature green synthesis method. Characterization of synthesized Pd NPs was carried out by UV–Vis spectrometry, Transmissive Electron Microscopy (TEM), X-ray diffraction (XRD), and Fourier Transform Infrared Spectroscopy (FTIR) techniques. According to TEM analysis, Pd NPs were confirmed to be in a spherical shape and the mean particle size was determined to be 4.11 nm. The crystal structure of Pd NPs was checked using XRD analysis and the mean particle size was observed to be 6.72 nm. Besides, the antibacterial activity of Pd NPs was determined against Escherichia coli (E. coli) (ATCC 8739), Bacillus subtilis (B. subtilis ATCC 6633), Staphylococcus aureus (S. aureus ATCC 6538), Klebsiella pneumoniae (K. pneumoniae ATCC 11296) and Serratia marcescens (S. marcescens ATCC) bacteria. Antibacterial activity was determined to be high in Pd NPs which is in conformance with the results acquired. The Pd NPs showed good photocatalytic activity, after 90 min illumination, about 81.55% and 68.45% of MB and MO respectively were catalysed by the Pd NPs catalyst, and 74.50% of RhB dyes were removed at 120 min of illumination. Within the scope of this project, it is recommended to use Pd NPs obtained by the green synthesis in the future as an antibacterial agent in biomedical use and for the cleaning of polluted waters. Graphical abstract: Image 1 Highlights: Biogenic Pd NPs were synthesized using lemon peels. The Pd NPs antibacterial activity was measured. The MBC and MIC values of Pd NPs were determined. The photocatalytic activity of Pd NPs against organic dyes was evaluated.